Planning for a successful Robotic Process Automation (RPA) project: a case study/ Dahlia Fernandez and Aini Aman - Fernandez, Dahlia; Aman, Aini (Faculty of Information Management, 2021)
The revolution of technology is often emphasized in any organization for them to remain competitive in the market. Among the latest technologies is Robotic Process Automation (RPA) which can mimic humans and take over their tasks. However, implementing RPA can turn into something complicated and challenging if it is implemented without proper strategic planning. Hence, this study aims to understand how to do proper planning in a successful Robotic Process Automation (RPA) project. This study uses an in-depth case study approach in one of the largest oil and gas organizations that provides F&A services. The result of the study showed that an effective RPA project should have careful planning as well as a realistic project planning timeline. The project timeline is very important to ensure that the project remains transparent and organized. Besides that, clear communication is very important to employees so that they can accept the changes that are taking place. It is also important for the employee to receive strong support from the management and information technology (IT) department for a successful implementation of the RPA project.